KEUNTUNGAN MAKSIMAL DARI PENJUALAN MARTABAK MANIS DENGAN MENGGUNAKAN METODE SIMPLEKS DAN SOFTWARE POM-QM - Luki Luki; Velagia Pitri; Teodora Tri Haryuni; Ventalia Ventalia; Jovani Jovani; Laurensia Mutiara Salvi; Eric Julian; Dudy Effendy (LPPM Politeknik Pratama, 2022)
Martabak Manis is a kind of pancake food in the form of sweet rice flour dough which is baked and then given a topping and then folded. Almost all over Indonesia have sellers of this food, this is due to the soft and soft texture, with a sweet taste, so this type of martabak is very popular as a dessert. In addition, this sweet martabak is also preferred because it has various variants of toppings such as cheese, chocolate, peanuts, and many more so that buyers can choose and don't feel bored with this food quickly. However, in this business technique is required to be able to generate maximum profit or profit. In maximizing this profit, this used simplex method, where this method utilizes information technology, POM-QM to generate maximum profit.The result showed that the seller had to produce three times sweet martabak with cheese toppings to get a maximum profit Rp 10.200.000 per month obtained from X2=3 times.